(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Film and documentary films have a critical force and effect on public discourse and formal pedagogic methods. A documentary’s substance and message may be seen as the ’truth.’ This is usually based on the idea that because the documentary is focused on a genuine occurrence, it aims to objectively highlight important problems and difficulties to show the truthfulness of the under examination phenomena. This article explores the introduction, Can The Goddess Speak, Draupadi The Exotic, Gods, Lovers, And Brothers, Dopdi Unbound, Persisting Ideologies, Exceptional Women.